Country risk and stock market volatility in Africa: Measuring the contribution of political and economic risk factors - Hoveni, Jamela Basani (Rhodes University, Faculty of Commerce, Department of Economics and economic History)
Thesis embargoed. To be released in 2025.
Keywords: Uncatalogued